Activation of Vegetable Oils by Reaction with Maleic Anhydride as a Renewable Source in Chemical Processes: New Experimental and Computational NMR Evidence - Francesco Lanero; Bianca Maria Bresolin; Anna Scettri; Marco Nogarole; Elisabetta Schievano; Stefano Mammi; Giacomo Saielli; Alessia Famengo; Alessandra Semenzato; Giovanni Tafuro; Paolo Sgarbossa; Roberta Bertani (Molecules, 2022)
Vegetable oils are bio−based and sustainable starting materials that can be used to develop chemicals for industrial processes. In this study, the functionalization of three vegetable oils (grape, hemp, and linseed) with maleic anhydride was carried out either by conventional heating or microwave activation to obtain products that, after further reactions, can enhance the water dispersion of oils for industrial applications. To identify the most abundant derivatives formed, trans-3-octene, methyl oleate, and ethyl linoleate were reacted as reference systems. A detailed NMR study, supported by computational evidence, allowed for the identification of the species formed in the reaction of trans-3-octene with maleic anhydride. The signals in the 1H NMR spectra of the alkenyl succinic anhydride (ASA) moieties bound to the organic chains were clearly identified. The reactions achieved by conventional heating were carried out for 5 h at 200 °C, resulting in similar or lower amounts of ASA units/g of oil with respect to the reactions performed by microwave activation, which, however, induced a higher viscosity of the samples.